Jurisprudential fabrication and Its Applications to the Oath of Invocation According to the Practice in Jordanian Sharia Courts - Aljourneh, Osama; Hazaimeh, Hamza; Amawi, Qais (Jordan Journal of Islamic Studies, 2023)
This study highlights the legal jurisprudential issue that arises in Sharia courts, derived from the provisions of the Journal of Judicial Judgements, which is a question of the "Oath of Invocation." It also examines the jurisprudential concept of fabrication, identifying the scholars who permit it, its relation to the concept of facilitation in Islamic law, the conditions for its application, its historical emergence, types, categories, and criteria. The study further highlights the application of the jurisprudential fabrication in Article 1746 of the Judicial Decisions Journal as practiced by the Journal of Judicial Judgements, discussing the necessity and justification for its application. Additionally, it explores the scholars who oppose its permissibility and clarifies the religious obligations regarding its application. The jurisprudential oath is then applied in the context of the "judgment against the non-concealing opponent" and supported by a series of appellate decisions related to the legitimate forensics oath in cases involving inheritance debts. Finally, the study concludes with key findings and recommendations.